Application of collaborative modelling method in Pile-Beam-Arc of Subway station. Issue 3 (August 2020) - Luo, Qingfei; Cao, Quan; Li, Wei; Zhao, Chunsheng; Xue, Qingwei; Zhang, Mengheng; Shen, Peng
Abstract: Taking Pile-Beam-Arc of Harbin Metro Line 2 Shengzhengfu station as an example, through the Midas GTS NX, different methods are used to establish the numerical model of PBA method. The results show that the quality of the model generated by the collaborative modelling method is better and the modelling efficiency is higher. The specific embodiment is that the number of units generated by the collaborative modelling method is less than that of auto-solid method, and the operation time of the model is reduced. The quality of the model generated by the collaborative modelling method is better than that of auto-solid method, which improves the model convergence and accuracy. The efficiency and application conditions of collaborative modelling method are better than those of plane element expansion method.